Peta Pemikiran Keagamaan Islam di Indonesia; Dampak Positif dan Negatif bagi Umat - Musthofa Musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2015)
Judging by the more fundamental in the religious thought of Islam in Indonesia is multi dimensial that will get some variants ratio of absolute thought. It is actually not a paradigm, because in the social sciences there must be various paradigms, not mutually exclusive, but rather mutually clump together, although there are three forms of social thought of Islam, which is called by wearing their own terms, as "Islam Rational", "Islamic Civilization ", and" Transformative Islam ". The existence of three models of Islam was through this paper, could be considered as a term Imere Lakatos, by a research program. Elite figures are among Muslim schoolars. Mapping of Islamic thought will have an impact on the understanding of different and will affect the attitudes, behavior of someone who made of the results of that thinking. The possitive impact understanding make an alternative range of ideas that lead to manifold understanding was so people can have a diversity of understanding it in accordance with the demands of his conscience, respect the opinion of the ideas of others so happens tolerance view of thinking one people with another in the other group or individual if his diverse and united understanding will foster the people ideas who agree to bring unity and unity too. Â Â Â Â Â The negative impact understanding of variant thought make the people will appear understanding of fanaticism to the ideas of a person because a person's thoughts will always experience a shift in accordance with the phenomena encountered, there is a tendency lack of respect for the opinions of others when thinking is considered the most correct, because everybody tends for his opinion is the result of thinking, of course, a result of the ideas that will shape the character variant for different people so they tend to form groups of thought that are difficult to integrate.